Peningkatan Kolaborasi Institusi Akademik Antar Negara Untuk Peningkatan SDM Masyarakat Perbatasan - Nurul Bariyah; Rosyadi, Rosyadi; Jumhur, Jumhur; Putra, Windhu; Suradi, Romi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The border region between Indonesia and Malaysia has unique characteristics and great development potential. Border communities face special challenges related to limited access to resources and development opportunities. Based on the Key Performance Indicator (IKU) of PTN number 6 which shows a focus on cooperation and collaboration between study programs and partners at the international level. FIBAA accreditation requires universities to be able to improve their international reputation and the attractiveness of their educational programs. International cooperation can be an important factor in obtaining accreditation from FIBAA. This cooperation can provide additional value and provide certain benefits, especially if it involves leading institutions. Therefore, the PKM Team conducted benchmarking to the Faculty of Economics and Business, Universiti Malayasia Sarawak. The results of the discussions that had been carried out obtained the result that FEB Unimas agreed to the international cooperation between the Department of Economics and Development Studies, FEB Untan and FEB Unimas. This agreement opens up opportunities to improve the quality of education, research, and development in both institutions. The potential for international cooperation between FEB Unimas and FEB Untan is very positive, especially in improving the quality of education for Human Resources in border areas through scholarship and student exchange programs, skills and competency development, and increased research and innovation.